Online Reputations: Comparing Hospital- and Patient-Generated Ratings in Academic Otolaryngology. (December 2021) - Basa, Krystyne; Jabbour, Nicolette; Rohlfing, Matthew; Schmoker, Sarah; Lawlor, Claire M.; Levi, Jessica; Sobin, Lindsay; Tracy, Jeremiah C.; Tracy, Lauren F.
Objectives: This study compares hospital-generated online ratings to patient-generated online ratings in academic otolaryngology and evaluates physician factors influencing these results. Methods: Websites of academic otolaryngologists were assessed for inclusion of hospital-generated Press Ganey surveys. Corresponding scores on Healthgrades andVitals.com were identified via internet search. Hospital ratings were compared with patient-generated ratings, including score, demographics, and number of ratings. All data was collected between July 15th 2019 and August 22nd 2019. Results: 742 academic otolaryngologists with hospital-generated ratings were identified. Mean hospital-generated rating was significantly higher ((4.70, 95% CI 4.69-4.72) than patient-generated rating (Vitals:4.26, 95% CI 4.18-4.34, and Healthgrades:4.02, 95% CI 3.87-4.18; P  < .001). In patient-generated rating, an increased number of rating scores (>20) was associated with male gender, professor ranking, and >30 years in practice ( P  < .005). Physician demographics did not impact number of ratings in hospital-generated setting. With patient-generated, lower aggregate score was associated with professor ranking ( P  = .001). In hospital-generated, lower score was associated with >30+ years in practice ( P  = .023). Across all platforms, comprehensive otolaryngologists and neurotologists/otologists were rated lower in comparison to other specialties (PGS: P  < .001, Vitals: P  = .027, Healthgrades: P  = .016). Conclusion: Hospital-generated ratings yield higher mean scores than patient-generated platforms. Between sources, Healthgrades.com scores were lower than those ofVitals.com . Professors with >30 years of practice generated more reviews in patient-generated ratings, and these physicians were generally rated lower. Access to patient-generated ratings is universal and physicians should be aware of variability between online rating platforms as scores may affect referrals and practice patterns.